2010
DOI: 10.5114/aoms.2010.13885
|View full text |Cite
|
Sign up to set email alerts
|

Basic research Co-culture with Schwann cells is an effective way for adipose-derived stem cells neural transdifferentiation

Abstract: IntroductionAdipose-derived stem cells (ADSCs) could accomplish neural transdifferentiation with the presence of certain growth factors in vitro. It has been proved that bone marrow stromal cells (BMSCs) can realize neural transdifferentiation only by being co-cultured with Schwann cells (SCs), and in our former studies we have confirmed that ADSCs could do so too. This paper aims to investigate whether the neural induction efficiency of co-culture is as high as that of other strategies using chemicals or chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Unfortunately, autologous SCs isolation is an invasive procedure and it is difficult to get sufficient number of SCs for clinical application. However, recent studies demonstrated that ADSCs seems to be one ideal cell source for transdifferentiation into SCs [40]. In our previous study, using a standard protocol, ADSCs were induced into SCs [22].…”
Section: Transdifferentiation Potential Of Adscs Into Schwann Cells Amentioning
confidence: 97%
“…Unfortunately, autologous SCs isolation is an invasive procedure and it is difficult to get sufficient number of SCs for clinical application. However, recent studies demonstrated that ADSCs seems to be one ideal cell source for transdifferentiation into SCs [40]. In our previous study, using a standard protocol, ADSCs were induced into SCs [22].…”
Section: Transdifferentiation Potential Of Adscs Into Schwann Cells Amentioning
confidence: 97%
“…These unique biological properties of MSCs highlight great potential in several applications such as regenerative medicine, tissue engineering and cell-based therapy. Here, this review focuses on an overview of MSCs biological International Society for Cellular Therapy (ISCT) has proposed minimal criteria for defining MSCs in 2006 [20]. The characteristics of MSCs can be described at least 3 definitions as followed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively small number of ADSC to explain the overall functional recovery in the reported studies, their presence signifies "transdifferentitation" as a possible mechanism underlying the positive therapeutic impact (Gutierrez-Fernandez et al 2013a). Indeed, the capacity of neural differentiation for ADSC has been extensively investigated (Cardozo et al 2010;Kompisch et al 2010;Liao et al 2010;Qian et al 2010;Abdanipour et al 2011;Yu et al 2011;Ahmadi et al 2012). It has also been reported that, compared with bone marrow-derived mesenchymal stem cells, ADSC have superior neurogenic potential (Kang et al 2004).…”
Section: Transdifferentiationmentioning
confidence: 99%